Purification and partial characterization of cathepsin D from porcine (Sus scrofa) liver using affinity chromatography - Canduri, F.; Ward, R. J.; de Azevedo, W. F.; Gomes, RAS; Arni, R. K. (Academic Press Aust, 1998)
Cathepsin D, a lysosomal aspartic protease, has been purified from porcine liver using a combination of pepstatin-A agarose and Affi-Gel Blue affinity chromatography, followed by size-exclusion chromatography. The purified protein consists of two polypeptide chains of 15 and 30 kDa, and has an isoelectric point of 6.8. Porcine liver cathepsin D has maximum activity at pH 2.5-3.0 as determined by its activity against hemoglobin, with a K-cat of 14.3 s(-1) and a k(cat)/K-M of 2.70 x 10(6) s(-1) M-1 as determined by the hydrolysis of a fluorogenic peptide substrate.
Keywords: cathepsin D; aspartic protease; lysosomal enzyme; affinity chromatography; pepstatin A